Reduced Medial Prefrontal Cortex Volume in Adults Reporting Childhood Emotional Maltreatment - van Harmelen, Anne-Laura; van Tol, Marie-José; van der Wee, Nic J.A.; Veltman, Dick J.; Aleman, André; Spinhoven, Philip; van Buchem, Mark A.; Zitman, Frans G.; Penninx, Brenda W.J.H.; Elzinga, Bernet M. (Biological psychiatry (1969), 2010)
Childhood emotional maltreatment (CEM) has been associated with a profound and enduring negative impact on behavioral and emotional functioning. Animal models have shown that adverse rearing conditions, such as maternal separation, can induce a cascade of long-term structural alterations in the brain, particularly in the hippocampus, amygdala, and prefrontal cortex. However, in humans, the neurobiological correlates of CEM are unknown. Using high-resolution T1-weighted 3T magnetic resonance imaging, anatomical scans and a whole-brain optimized voxel-based morphometry approach, we examined whether healthy control subjects and unmedicated patients with depression and/or anxiety disorders reporting CEM before age 16 ( n = 84; age: mean = 38.7) displayed structural brain changes compared with control subjects and patients who reported no childhood abuse ( n = 97; age: mean = 36.6). We found that self-reported CEM is associated with a significant reduction in predominantly left dorsal medial prefrontal cortex volume, even in the absence of physical or sexual abuse during childhood. In addition, reduced medial prefrontal cortex in individuals reporting CEM is present in males and females, independent of concomitant psychopathology. In this study, we show that CEM is associated with profound reductions of medial prefrontal cortex volume, suggesting that sustained inhibition of growth or structural damage can occur after exposure to CEM. Given the important role of the medial prefrontal cortex in the regulation of emotional behavior, our finding might provide an important link in understanding the increased emotional sensitivity in individuals reporting CEM.